PO.2.48 Incomplete systemic lupus erythematosus: clinical and immunological manifestations. (27th September 2022) - Panafidina, T; Popkova, T; Kondrateva, L; Gorbunova, Y; Nasonov, E; Lila, A
Abstract : Purpose: Incomplete systemic lupus erythematosus (iSLE) is a condition of patients with clinical and immunological signs of lupus who do not fulfill classification criteria for SLE. Methods: All patients were admitted to V.A.Nasonova Research Institute of Rheumatology between January 2018 and December 2021. A total of 42 patients were enrolled in the iSLE group. iSLE was defined by rheumatologists as clinical diagnosis, not fulfilling ACR 1997 or SLICC 2012 criteria (<4 criteria) and had no classification or specific symptoms of other rheumatic diseases. The majority of the iSLE patients were female (98%), aged 38[27–48]years (median [interquartile range 25%-75%]). Results: The median age of iSLE diagnosis was 33[26–43]years, the appearance of the first clinical or immunological manifestations at the age 30[22–40]years. In the most patients, there were no connection with any provoking factors – 57%, in 20%pts the iSLE onset was associated with pregnancy, in 10%-with infection, 5% each-with combined oral contraceptives use and insolation. The median disease duration was 15[2–48]months, 10(24%)pts had a disease duration of ≥5 years. At the onset of iSLE diagnosis, the most patients had clinical and immunological signs-74%, clinical only-14%, immunological only-12%pts. The clinical manifestations were as follows: fever – 33%, leukopenia – 19%, thrombocytopenia – 17%, autoimmune hemolysis – 2%, psychosis – 5%, migraine – 19%, acute cutaneous lupus – 17%, subacute/discoid cutaneous lupus – 2%, panniculitis-2%, non-scarring alopecia – 5%, Raynaud phenomenon-2%, oral ulcers – 2%, pleural or pericardial effusion – 12%, joint involvement – 45%, nephritis – 12%. Autoantibody profiles revealed the presence of ANA in 83% cases, anti-dsDNA - in 45%, anti-Sm - none, antiphospholipid antibodies(aPL) – in 38% of patients. Fifteen patients (36%) exhibited low complement. Evolution of iSLE to SLE occurred in 12(28%) of these patients, 1(2%)- to antiphospholipid syndrome, 2(5%) – to osteoarthritis, 6(14%) - to none-rheumatic diseases, with a median interval of 19[8–48]months between iSLE onset and the other definite diagnosis. The majority (50%) of patients continue to be observed by a rheumatologist with a diagnosis of iSLE. Conclusions: The vast majority of patients with iSLE have a combination of clinical and immunological lupus symptoms. The most commonly occurring clinical features are joint involvement, fever, leukopenia, thrombocytopenia and acute cutaneous lupus. The most common immunological disorders are positive ANA and anti-dsDNA, more than a third of iSLE patients had aPL and hypocomplementemia. A significant number of patients with iSLE, however, have serious organ involvement: nephritis (12%), serositis (12%), and up to 5% have neurologic symptoms. This may explain why many iSLE patients should be treated with immunomodulatory medications. Therapeutic intervention during the preclassification period could delay SLE onset and reduce organ damage.